2020
DOI: 10.7717/peerj.8675
|View full text |Cite
|
Sign up to set email alerts
|

Native bees of high Andes of Central Chile (Hymenoptera: Apoidea): biodiversity, phenology and the description of a new species ofXeromelissaCockerell (Hymenoptera: Colletidae: Xeromelissinae)

Abstract: High-altitude ecosystems are found in mountain chains and plateaus worldwide. These areas tend to be underrepresented in insect biodiversity assessments because of the challenges related to systematic survey at these elevations, such as extreme climatic and geographic conditions. Nonetheless, high-altitude ecosystems are of paramount importance because they have been seen to be species pumps for other geographic areas, such as adjacent locations, functioning as buffers for population declines. Moreover, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(85 reference statements)
1
3
0
1
Order By: Relevance
“…Blaauw & Isaacs, 2014). A stronger season than treatment effect was also observed by the end of season (autumn) when wild bees are finishing their life-cycles as has been documented in other places in Central Chile (Henríquez-Piskulich et al, 2020). Wild bees were abundant in summer, which indicates that NFS are important for maintaining flower resources in agricultural landscapes beyond the period of crop flowering.…”
Section: Discussionsupporting
confidence: 55%
“…Blaauw & Isaacs, 2014). A stronger season than treatment effect was also observed by the end of season (autumn) when wild bees are finishing their life-cycles as has been documented in other places in Central Chile (Henríquez-Piskulich et al, 2020). Wild bees were abundant in summer, which indicates that NFS are important for maintaining flower resources in agricultural landscapes beyond the period of crop flowering.…”
Section: Discussionsupporting
confidence: 55%
“…There is still considerable turnover, unique diversity and localized endemism within all the proposed WBE, and this is likely because of conserved traits among species that facilitate their persistence in varying habitats and climates (Villalobos and Vamosi 2018) but may also reflect a lack of sampling and digitization in the understudied areas. There is preliminary evidence for a latitudinal and elevation relationship in rates of turnover; the northern and eastern WBE both for Central and Northern (CQ, CA, AE), show higher turnover between sites compared to the more southern, lower elevation WBE, reflecting a higher exchange and filtering of species (Hodkinson, 2005;Hoiss et al, 2012) as has been observed in for bees in the central Chilean Andes (Henríquez-Piskulich et al, 2020). In contrast to the results observed for compositional dissimilarity, we did not observe such a strong variation in phylogenetic diversity metrics between WBE.…”
Section: Discussionmentioning
confidence: 87%
“…The east-west transition to the Central Andes bee eco-region follows the transition zone between the Central Chilean Subregion and the South American transition zone, and follows the Central Andean Cordillera proposed by Peña (1966), with a highly distinctive fauna and vegetation (Arroyo et al, 1982). The Chilean Andes are, almost certainly, home to many undescribed and undigitized bee species especially given the high diversity found in other parts of the Andes (Henríquez-Piskulich et al, 2020, Gonzalez and Engel 2004). This is supported by two recently described Colletes species endemic to the Central Andes WBE; Colletes flavipilosus Ferrari, 2017 (Hymenoptera: Colletidae), and Colletes guanta (Ferrari 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The east–west transition from CV to CA is comparable to the transition zone between the Central Chilean subregion and the South American transition zone, while CA is analogous to the Central Andean Cordillera proposed by Peña (1966). It has a distinct fauna and vegetation (Arroyo et al, 1982) and likely contains many undescribed and undigitized bees, similar to other parts of the Andes (Gonzalez & Engel, 2004; Henríquez‐Piskulich et al, 2018, 2020).…”
Section: Discussionmentioning
confidence: 99%